Pragmatic but Principled: Background report on Integrated Water Resource Management - Heath, Tom (Cranfield University, 2010)
IWRM is about integrated and "joined-up" management. It is about promoting integration across sectors, applications, groups in society and time, based upon an agreed set of principles. IWRM has been widely applied and aims for more coordinated use of land and water and is divided into full (wholly integrated activities) and light (applying the principles at the local level). The main criticisms of IWRM are the failure to translate the theory into action and the lack of change on the ground. There is a need for both light and full IWRM, but future projects need to increase participation and engagement.